KONFLIK BATIN TOKOH-TOKOH NOVEL LELAKI YANG SETIA MENCUMBUI SENJA KARYA ANDI ZULFIKAR - Dewicahya, Gusti Ayu Gita (Humanis, 2013)
This article analysis the inner conflicts of the characters novel Lelaki yang Setia Mencumbui Senja (Faithful Man Fondle Twilight) written by Andy Zulfikar. This novel interesting to an analysis, because more emphasize the psychological aspects.Theory used there are two kinds, there are  the theory of structural and theory of  psychology literature. The primary character, namely Said  have inner conflict when he had to accept the fact that he is not biological children of Mrs. Maryam. However, Said continued resilient under going living and struggling to achieve his ideals. Mrs. Maryam also has a inner conflict when she was unable to conceal the real identity of Said. With his diligence, now Said can be able to achieve his dream and he could meet with his biological parents who had been separated. From the Said of a life story can be concluded that life is a big struggle. This novel provides inspiration on how to achieve success with fighting and trying.
Keywords: structural, psychology, and inner conflict